Utility of BBCR in Case of Dyspnoea: A Case Report (Advancements in Homeopathic Research, 2023)
Dyspnoea is shortness of breath or a feeling that you  cannot breathe enough air into lungs which can cause  tightness in chest. Dyspnoea can be due to exercise  which is short term or due to some underlying  causes such as respiratory, cardiac, neuromuscular,  psychogenic, systemic illness, or their combination.1This article deals with case reported to us with  dyspnoea since 3 year. After detailed case taking  and repertorisation of case by Boger Boennighausen  Characteristics and repertory2, Ipecacuhana was  prescribed on the basis of repertorization and in 2  months patient was relieved from her complaints. The  assessment was done on Modified Borg Dyspnoea  Scale3 and pre treatment it was 5 and post treatment  after 2 months 0.5 which shows marked improvement  in Dyspnoea.
Keywords: Dyspnoea; Boger Boennighausen Characteristics and repertory; Ipecacuhana; Reperorization